PELATIHAN PEMBUATAN SABUN CUCI PIRING PADA KELOMPOK TANI RINGIN ASRI DESA KEDUNG BANTENG – KEC. SUMBERMANJING WETAN – KAB. MALANG - Prayitno; Arief Rahman Hakim; Luchis Rubianto; Susanto (Jurnal Pengabdian kepada Masyarakat, 2022)
Ringin Asri Farmer Group – Kedung Banteng Village is one of the potential farmer groups which is indicated by the many activities carried out, including: sales of agricultural products such as fertilizers, insecticides, agricultural medicines and household necessities such as bath soap, dish soap , hand soap, toothbrush and others. The goods sold in this farmer group are obtained from large markets in Dampit, Turen and Malang. With the location of Sumbermanjing Wetan Village which is relatively far from urban areas, the prices of these goods become more expensive, even though soap products can be made by farmers using very simple technology. On the other hand, the teaching staff at the Department of Chemical Engineering – State Polytechnic of Malang already have the knowledge and skills in making dish soap and implementing the manufacture of dish washing in entrepreneurship courses. The purpose of community service (PPM) is to provide/transfer experience and skills in making and entrepreneurship of dish soap to the Ringin Asri Farmer Group - Kedung Banteng Village - Kec. Sumbermanjing Wetan. This PPM activity was carried out at the Kedung Banteng Village Hall using the lecture, discussion and practice of making dish soap. The results of the PPM showed that the participants interest, enthusiasm for participating in the activity was very high, which was indicated by the ability of participants to make dish soap independently and the results of the questionnaire given, where 95% of participants stated that they were very satisfied